Wording time: notes on the experience of a visual arts internship in a Laboratory School (Revista Apotheke, 2025)
This article is composed of words, sensations and reflections made during the experience of the internship in visual arts at João XXIII Laboratory School (managed by Federal University of Juiz de Fora). It is the writing of a future educator in dialogue with the institution's teaching staff, aspiring to build shareable knowledge about time, time in school and time in the art class. These themes are treated through personal accounts intermingled with the knowledge of experience, which sprouts out of, mainly, the reading of Jorge Larrosa.
Keywords: time in school; time in arts class; laboratory school; supervised internship; experience